2018
DOI: 10.3390/app8101889
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on Anti-Icing Performance of NS-DBD Plasma Actuator

Abstract: An experimental study was conducted to evaluate the anti-icing performance of NS-DBD plasma actuator under the conditions of airflow speed U = 65 m/s, ambient temperature T = −10 °C, liquid water content LWC = 0.5 g/m3, mean-volume diameter MVD = 25 μm, mainly to clarify the effect of pulse frequency and voltage amplitude of actuation on anti-icing performance. A NACA0012 airfoil model with a chord length of c = 280 mm was used in the tests. The NS-DBD plasma actuator was mounted at the front part of the airfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 41 publications
1
13
0
Order By: Relevance
“…Whereas the related topic of plasma actuators (PA) for flow control applications is widely studied [9][10][11][12][13][14][15][16][17][18][19][20], there is recently a growing interest in the study of surface dielectric barrier discharges (SDBDs) as an anti-icing and de-icing system [21][22][23][24][25][26][27][28][29][30]. Probably Meng et al [24] and Cai Jinsheng et al [21] were the first who reported experimental results indicating that SDBDs can work as an anti/de-icing system.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas the related topic of plasma actuators (PA) for flow control applications is widely studied [9][10][11][12][13][14][15][16][17][18][19][20], there is recently a growing interest in the study of surface dielectric barrier discharges (SDBDs) as an anti-icing and de-icing system [21][22][23][24][25][26][27][28][29][30]. Probably Meng et al [24] and Cai Jinsheng et al [21] were the first who reported experimental results indicating that SDBDs can work as an anti/de-icing system.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the DBDPA has attracted significant attention in thermo-fluid engineering [16][17][18][19][20][21][22][23][24][25][26]. The enhancement of convective heat transfer using ionic wind for high-temperature wall cooling has been shown to be promising [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, electro-thermal systems require in general materials with high thermal conductivity, which is inapplicable to the new generation erosion resistant polymers [58]. Another option for active icing protection is via mechanical vibrations excited through ultrasonic, piezoelectric or dielectric actuators [59][60][61][62]. Despite of consuming less energy, the efficiency of mechanical approach is highly restricted due to insurmountable inherent energy losses in the actuator, reducing the amplitude of mechanical oscillations applied to destroy the ice bonds.…”
Section: Active and Passive Anti-icing/de-icing Methods-critical Overmentioning
confidence: 99%